THE ECONOMIC IMPORTANCE AND SCOPE OF USE OF TRANSPORT LOGISTICS (Conferencea, 2024)
In this article, the role of transport Logistics in creating economic importance, scope and value of use was studied. The idea was made about the peculiarities of the services of logistics of the Transport process. It depends on the efficiency of transportation service, storage operations, container and packaging, documentation and other intermediary mobility. Information is provided about the impact of transit, warehouses, loading and unloading and other operations on the formation of the competitiveness of the enterprise.